2007
DOI: 10.1080/00016340601110721
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of vulvovaginal erosive and stenosing lichen planus by surgical dilatation and methotrexate

Abstract: We treated five patients with stenosing lichen planus [LP] of the vulvovaginal region with methotrexate supplemented with ultrapotent corticosteroid cream and tacrolimus, in combination with surgical dilatation. All patients experienced long-term symptom relief, and there was only minimal or moderate re-stenosing of the vagina on follow-up for 2-41 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 30 publications
(28 reference statements)
1
15
0
Order By: Relevance
“…51 In a retrospective selfadministered survey, 11 women who had undergone surgery for VVLP-associated adhesions, 55% of patients were able to engage in sexual intercourse and were sexually active, whereas 75% had decreased urinary symptoms or infections. All patients reported symptomatic relief and only minimal to moderate restenosis of the vagina after 2 to 41 months.…”
Section: Medical Therapymentioning
confidence: 99%
“…51 In a retrospective selfadministered survey, 11 women who had undergone surgery for VVLP-associated adhesions, 55% of patients were able to engage in sexual intercourse and were sexually active, whereas 75% had decreased urinary symptoms or infections. All patients reported symptomatic relief and only minimal to moderate restenosis of the vagina after 2 to 41 months.…”
Section: Medical Therapymentioning
confidence: 99%
“…Isolated surgical procedures will not help and will invariably lead to further scarring of the vagina. In a small series of five patients, improvement was seen after treatment with topical steroids, tacrolimus ointment, methotrexate and surgical dilatation (Kortekangas-Savolainen & Kiilholma 2007). Regular sexual intercourse will help to preserve patency, but is often impractical because of dyspareunia.…”
Section: Managementmentioning
confidence: 99%
“…15 In another case series, the combination of oral methotrexate 7.5 mg once weekly supplemented with local ultrapotent corticosteroid cream and tacrolimus, together with surgical dilation was effective in the treatment of five patients with severe erosive and stenosing vulvovaginal LP. 16 In a retrospective study, oral methotrexate 2.5-12.5 mg once weekly was found to have substantial activity in erosive oral LP, particularly in those patients with treatment refractory and aggressive disease. 17 In all of these studies, low doses of methotrexate were used with marked improvement in genital and/or oral symptoms supported by physical findings.…”
Section: Discussionmentioning
confidence: 99%
“…7,13 Three publications have suggested that methotrexate might have some promise in managing this debilitating condition. [15][16][17] Although the aetiology of LP is unknown, an autoimmune pathogenesis is postulated with activated T-cells directed against basal keratinocytes. 18 On this basis, methotrexate would be helpful in the treatment of this condition through down-regulation of an immunologically mediated mucosal response.…”
Section: Discussionmentioning
confidence: 99%